Groundwater monitoring and modelling of the “Vector” site for near-surface radioactive waste disposal in the Chornobyl exclusion zone - D. Bugai; A. Skalskyy; K. Haneke; S. Thierfeldt; O. Nitzsche; A. Tretyak; Yu. Kubko (Ядерна фізика та енергетика)
Results of purposeful groundwater monitoring and modelling studies are presented, which were carried out in order to better understand groundwater flow patterns from the “Vector” site for near-surface radioactive waste disposal and storage in the Chornobyl exclusion zone towards river network. Both data of observations at local-scale monitoring well network at “Vector” site carried out in 2015 - 2016 and modelling analyses using the regional groundwater flow model of Chornobyl exclusion zone suggest that the groundwater discharge contour for water originating from “Vector” site is Sakhan River, which is the tributary to Pripyat River. The respective groundwater travel time is estimated at 210 - 340 years. The travel times in subsurface for 90Sr, 137Cs, and transuranium radionuclides (Pu isotopes, 241Am) are estimated respectively at thousands, tenths of thousands, hundreds of thousands – million of years. These results, as well as presented data of analyses of lithological properties of the geological deposits of the unsaturated zone at “Vector” site, provide evidence for good protection of surface water resources from radioactivity sources (e.g., radioactive wastes) to be disposed in the near-sursface facilities at “Vector” site.